Effects of Low Molecular Weight Heparin and Unfragmented Heparin on Induction of Osteoporosis in Rats - Mätzsch, Thomas; Bergqvist, David; Hedner, Ulla; Nilsson, Bo; Østergaar, Per (Thrombosis and Haemostasis, 1990)
A comparison between the effect of low molecular weight heparin (LMWH) and unfragmented heparin (UH) on induction of osteoporosis was made in 60 rats treated with either UH (2 IU/ g b w), LMWH in 2 doses (2 Xal U/g or 0.4 Xal U/g) or placebo (saline) for 34 days. Studied variables were: bone mineral mass in femora; fragility of humera; zinc and calcium levels in serum and bone ash and albumin in plasma. A significant reduction in bone mineral mass was found in all heparin-treated rats. There was no difference between UH and LMWH in this respect. The effect was dose-dependent in LMWH-treated animals. The zinc contents in bone ash were decreased in all heparin-treated rats as compared with controls. No recognizable pattern was seen in alterations of zinc or calcium in serum. The fragility of the humera, tested as breaking strength did not differ between treatment groups and controls. In conclusion, if dosed according to similar factor Xa inhibitory activities, LMWH induces osteoporosis to the same extent as UH and in a dose-dependent manner. The zinc content in bone ash was decreased after heparin treatment, irrespective of type of heparin given.